2015
DOI: 10.1007/s10965-015-0701-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of silica and novel functionalized silica-based cellulose acetate hybrid membranes in gas permeation study

Abstract: Cellulose acetate (CA) is a widely applied glassy polymer in the preparation of gas separation membranes. In the present study, hybrid membranes were prepared by incorporating silica (Si) and silica functionalized with ptetranitrocalix[4]arene (Si-CL) into the CA matrix, and their gas permeation abilities were explored with regard to CO 2 , N 2 and CH 4 gases. The diffusion-induced phase separation (DIPS) method was adopted to make pure CA, CA/Si, and CA/Si-CL hybrid membranes. The concentration of Si-CL was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The most intense peaks (equal intensity for all membranes in series 1) are the CA peaks found at 1045 and 1232 cm −1 , which are assigned to acetate groups (symmetric (ν s COC) and antisymmetric (ν as COC) modes, respectively [ 39 , 40 ]). The band centered at 1369 cm −1 is assigned to δ s CH 3 , and the band centered at 1741 cm −1 is assigned to the strong carbonyl stretching mode (νC=O) [ 41 , 42 ]. The broad band located at 3000–3700 cm −1 (assigned to the O–H stretching mode, νOH) [ 39 ] contains contributions from water (H–O–H), hydrolyzed silica/titania precursors (≡Si–OH − , ≡Ti–OH − ), and non-esterified cellulose polymer –OH groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most intense peaks (equal intensity for all membranes in series 1) are the CA peaks found at 1045 and 1232 cm −1 , which are assigned to acetate groups (symmetric (ν s COC) and antisymmetric (ν as COC) modes, respectively [ 39 , 40 ]). The band centered at 1369 cm −1 is assigned to δ s CH 3 , and the band centered at 1741 cm −1 is assigned to the strong carbonyl stretching mode (νC=O) [ 41 , 42 ]. The broad band located at 3000–3700 cm −1 (assigned to the O–H stretching mode, νOH) [ 39 ] contains contributions from water (H–O–H), hydrolyzed silica/titania precursors (≡Si–OH − , ≡Ti–OH − ), and non-esterified cellulose polymer –OH groups.…”
Section: Resultsmentioning
confidence: 99%
“…Two important bands of CA/SiO 2 hybrid membranes are the ν(Si–O–Si) and ν(Si–O–C), observed at 1065 and 1118 cm −1 , respectively [ 24 ]. Lower intensity peaks are observed at 1433 and 1637 cm −1 (assigned to δCH 2 and δHOH, respectively) [ 41 , 42 ]. The weak band centered at 903 cm −1 confirms the presence of acetate methyl groups [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…It obviously shows that the diffused peaks probably due to the amorphous nature of CA and decreases the crystallinity through the hydrogen bonding between acetyl and hydroxyl groups. The diffraction pattern of HMO nanoparticles is not observed is indicated that the amorphous nature of CA is dominated …”
Section: Resultsmentioning
confidence: 98%
“…The strong peak around 1754 cm −1 was assigned to the stretching mode of the C = O bond and another peak at 1371 cm −1 showed the bending of the C‐CH 3 group. The characteristic peaks around 1237 and 1052 cm −1 were attributed to the asymmetric stretching of ether C‐O and C‐O‐C vibrations . The incorporation of TBP in the CTA polymer matrix (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peaks around 1237 and 1052 cm −1 were attributed to the asymmetric stretching of ether C-O and C-O-C vibrations. 23 The incorporation of TBP in the CTA polymer matrix ( Fig. 2c and d) resulted in the improved intensity of the pure CTA spectra.…”
Section: Characterization Of Prepared Composite Membrane Ftir Analysismentioning
confidence: 88%